Comparative Analysis of the Government Structure and Policies to Disaster Response Adopted by the BRICS: Perspectives from the COVID-19 Pandemic - Ana Paula Pereira Maiato Nascimento; Híngred Ferraz Pereira Resende; Tharcisio Cotta Fontainha (Journal of BRICS Studies)
Disasters have increased in severity, diversity, and frequency over the years. Consequently, disaster response requires the involvement of different stakeholders, which makes managing disaster and humanitarian operations a challenge. Thus, the present research aims to compare the government structure and policies of the BRICS countries (i.e., Brazil, Russia, India, China, and South Africa) to disaster response operations, particularly during the COVID-19 pandemic. The research adopts the case study by investigating official government documents and public information. The results identified that the BRICS developed: (i) a vertical and centralized coordination approach within their territories in response to the COVID-19 pandemic, (ii) some cases of independence and misalignment between national and local governments in response to the COVID-19 pandemic, and (iii) creation and adjustment of particular policies and programs for the pandemic period with little consideration of government structures and policies for disaster response developed before the COVID-19 pandemic. Future research might compare the response to other disasters faced by all the BRICS countries and collaboration opportunities among them.